Measurement of PCDD/FS emissions from a coal-fired power plant in Malaysia and establishment of emission factors - M. Mokhtar, Mutahharah (Dokuz Eylul Universitesi, 2013)
This paper presents the PCDD/Fs emissions measured from a coal–fired power plant in Malaysia. The study discusses partitioning of PCDD/Fs in particle and gas phase, effects of coal quality to PCDD/Fs formation, effects of air pollution control device (APCD) configuration to PCDD/Fs formation and establishment of emission factors of PCDD/Fs from the studied coal–fired power plant. The results presented in this study were mostly in good agreement with the previous works on PCDD/Fs emissions conducted in other countries. Laboratory analysis results showed that PCDFs were the dominant congeners. The emissions of PCDD/Fs were low which most probably due to the high combustion efficiency. The PCDFs/PCDDs ratio was more than 1 and PCDD/Fs were detected in fly ash, hence speculating that the formation of PCDD/Fs during coal combustion was mainly through de novo synthesis. Analysis on partitioning of PCDD/Fs showed that the compounds were mainly emitted in gas phase. This study also indicated that type of coal influenced the formation of PCDD/Fs during coal combustion where bituminous coal with high sulfur (S) content resulted in slightly lower PCDD/Fs emissions compared to sub–bituminous coal. It was also found that operation of flue gas desulfurization (FGD) reduced the emission of PCDD/Fs. The established emission factors for PCDD/Fs were in the range of 0.08 to 0.11 ng I–TEQ/kg.